Chronic systemic immune dysfunction in African Americans with small vessel-type ischemic stroke - Brown, Candice M. (Transl Stroke Res, 2015)
BACKGROUND: The incidence of small vessel-type (lacunar) ischemic strokes is greater in African-Americans compared to whites. The chronic inflammatory changes that result from lacunar stroke are poorly understood. To elucidate these changes, we measured serum inflammatory and thrombotic biomarkers in African-Americans at least 6 weeks post-stroke compared to control individuals. METHODS: Cases were African-Americans with lacunar stroke (n=30), and controls were age-matched African-Americans with no history of stroke or other major neurologic disease (n=37). Blood was obtained >6 weeks post-stroke and analyzed for inflammatory biomarkers. Freshly isolated peripheral blood mononuclear cells were stimulated with lipopolysaccharide (LPS) to assess immune responsiveness in a subset of cases (n=5) and controls (n=4). RESULTS: After adjustment for covariates, the pro-inflammatory biomarkers, soluble vascular cadherin adhesion molecule-1 (sVCAM-1) and thrombin anti-thrombin (TAT), were independently associated with lacunar stroke. Immune responsiveness to LPS challenge was abnormal in cases compared to controls. CONCLUSIONS: African-Americans with lacunar stroke had elevated blood levels of VCAM-1 and TAT and an abnormal response to acute immune challenge >6 weeks post-stroke, suggesting a chronically compromised systemic inflammatory response.